REsveratrol for VAscular cognitive impairment investigating cerebral Metabolism and Perfusion (REVAMP trial): a study protocol for a randomized, double-blind, placebo-controlled trial - Hattori, Yorito; Minami, Manabu; Omae, Katsuhiro; Yoshimoto, Takeshi; Abe, Soichiro; Yamamoto, Haruko; Iida, Hidehiro; Ihara, Masafumi (Frontiers in Nutrition, 2024)
Background: Carotid artery stenosis or occlusion (CASO) is a major cause of vascular cognitive impairment (VCI). There is currently no effective treatment for VCI induced by CASO. Resveratrol, a type of polyphenol, improves cognitive performance in rat CASO models via pleiotropic effects. Furthermore, we previously reported the longevity gene, SIRT1, which can be activated by resveratrol, improves cognitive and cerebral blood flow impairment in mouse CASO models by activating endothelial nitric oxide synthase. However, clinical evidence remains limited.The REsveratrol for VAscular cognitive impairment investigating cerebral Metabolism and Perfusion (REVAMP) trial is a randomized, double-blind, placebo-controlled trial involving patients with asymptomatic CASO. Each participant will receive either 150 mg/day of resveratrol or a placebo for 35 weeks. The primary objective is to determine whether resveratrol improves cognitive impairment, as assessed using the Alzheimer's Disease Assessment Scale-cognitive subscale 13. One of our secondary objectives is to determine whether resveratrol improves cerebral hemodynamic impairment as assessed via 15 O-gas positron emission tomography. We will recruit 100 patients (50 per group).Discussion: The REVAMP trial may provide valuable insights into new therapeutic options, as multitarget neuroprotection could potentially improve cognitive function along with enhancements in cerebral hemodynamic status in patients with asymptomatic CASO. Clinical trial registration: The REVAMP trial was prospectively registered in the Japan Registry of Clinical Trials (jRCTs051230013) on April 13, 2023.